Ecobat: An online resource to facilitate transparent, evidence‐based interpretation of bat activity data. Issue 2 (12th December 2017) - Lintott, Paul R.; Davison, Sophie; van Breda, John; Kubasiewicz, Laura; Dowse, David; Daisley, Jonathan; Haddy, Emily; Mathews, Fiona
Abstract: Acoustic surveys of bats are one of the techniques most commonly used by ecological practitioners. The results are used in Ecological Impact Assessments to assess the likely impacts of future developments on species that are widely protected in law, and to monitor developments' postconstruction. However, there is no standardized methodology for analyzing or interpreting these data, which can make the assessment of the ecological value of a site very subjective. Comparisons of sites and projects are therefore difficult for ecologists and decision‐makers, for example, when trying to identify the best location for a new road based on relative bat activity levels along alternative routes. Here, we present a new web‐based, data‐driven tool, Ecobat, which addresses the need for a more robust way of interpreting ecological data. Ecobat offers users an easy, standardized, and objective method for analyzing bat activity data. It allows ecological practitioners to compare bat activity data at regional and national scales and to generate a numerical indicator of the relative importance of a night's worth of bat activity. The tool is free and open‐source; because the underlying algorithms are already developed, it could easily be expanded to new geographical regions and species. Data donation is required to ensure the robustness of the analyses; we use a positive feedback mechanism to encourage ecological practitioners to share data by providing in return high quality, contextualized data analysis, and graphical visualizations for direct use in ecological reports. Abstract : Ecological practitioners survey bat activity to assess the level of development permitted at a site, but these surveys are not currently standardised, so site‐to‐site comparisons are not possible. Ecobat is a new online resource that standardizes bat activity and allows relative assessments to be made in a local and national context. This innovative tool enables practitioners and policymakers to make informed, defensible decisions about site development, policy, and conservation of protected bat species.